Using human intestinal biopsies to study the pathogenesis of irritable bowel syndrome. Issue 4 (14th February 2014) - Nasser, Y.; Boeckxstaens, G. E.; Wouters, M. M.; Schemann, M.; Vanner, S.
Abstract Background Although animal models of the irritable bowel syndrome (IBS) have provided important insights, there are no models that fully express the features of this complex condition. One alternative approach is the use of human intestinal biopsies obtained during endoscopic procedures to examine peripheral mechanisms in this disorder. These studies have served to confirm the existence of peripheral pathways in humans with IBS and have provided many new mechanistic insights. Two general approaches have been employed; one approach has been to examine the biological activity of mediators within the mucosal tissue of IBS patients and the other has been to examine changes in the structural properties of key signaling pathways contained within the biopsies. Using these approaches, important changes have been discovered involving the enteric nervous system and the extrinsic sensory pathway (dorsal root ganglia neurons), the immune system, and epithelial signaling in IBS patients compared to healthy subjects. Purpose This review will systematically explore these mechanistic pathways, highlight the implications of these novel findings and discuss some of the important limitations of this approach.